Transcriptomic Analysis of a Tertiary Relict Plant, Extreme Xerophyte Reaumuria soongorica to Identify Genes Related to Drought Adaptation - Shi, Yong (Public Library of Science, 2013)
BACKGROUND: Reaumuria soongorica is an extreme xerophyte shrub widely distributed in the desert regions including sand dune, Gobi and marginal loess of central Asia which plays a crucial role to sustain and restore fragile desert ecosystems. However, due to the lacking of the genomic sequences, studies on R. soongorica had mainly limited in physiological responses to drought stress. Here, a deep transcriptomic sequencing of R. soongorica will facilitate molecular functional studies and pave the path to understand drought adaptation for a desert plant. METHODOLOGY/PRINCIPAL FINDINGS: A total of 53,193,660 clean paired-end reads was generated from the Illumina HiSeq™ 2000 platform. By assembly with Trinity, we got 173,700 contigs and 77,647 unigenes with mean length of 677 bp and N50 of 1109 bp. Over 55% (43,054) unigenes were successfully annotated based on sequence similarity against public databases as well as Rfam and Pfam database. Local BLAST and Kyoto Encyclopedia of Genes and Genomes (KEGG) maps were used to further exhausting seek for candidate genes related to drought adaptation and a set of 123 putative candidate genes were identified. Moreover, all the C(4) photosynthesis genes existed and were active in R. soongorica, which has been regarded as a typical C(3) plant. CONCLUSION/SIGNIFICANCE: The assembled unigenes in present work provide abundant genomic information for the functional assignments in an extreme xerophyte R. soongorica, and will help us exploit the genetic basis of how desert plants adapt to drought environment in the near future.